PERLINDUNGAN HUKUM TERHADAP KONSUMEN PADA AKTIVITAS PASAR ONLINE - Masola, Gideon M (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: With technological advancements bringing a huge positive impact where technology consumers can easily share innovations and the latest information instantly without going through complicated and lengthy procedures like centuries ago. Law No. 8 of 1999 concerning Consumer Protection has been in effect for more than 25 years as a reference in the resolution of consumer disputes. The author uses a juridical descriptive research method, namely by examining the suitability of legal rules and facts that occur in society. In this study, the author wants to research about the legal protection of consumers in online market activities limited to how the regulation of legal protection of consumers in online market activities and whether Law No.8/1999 on Consumer Protection is still relevant to current technological developments. The results of this study are: First, regulations on how to regulate legal protection of consumers in online market activities are currently regulated by several laws and regulations. This overlap of rules means that this law has not been applied in cases of cybercrime, especially those related to personal data. Second, it is necessary to clarify the regulations that govern online market activities. With clear rules, both consumers and business actors in online market activities know how and to whom to make complaints.Keywords: Online Market Activity, Consumer Protection, Online Transaction Disputes.